A reiview of mangrove and seagrass ecosystem and their kinkage to fisheries and fisheries management (Food And Agriculture organization of the United Nations, 2013)
Content: introduction to commericial seaweeds; seadweeds used as a source of agar; agar; seaweeds used as a source of alginate...